Mahasiswa sebagai fasilitator perubahan ekonomi sirkular sosial berbasis sampah - Imam Sa'id Nurfrendi (Qualitative Research of Business and Social Sciences, 2025)
The application of digital technology strengthens the circular economy in rural areas, as illustrated by a case study of the Zerowastemate application implemented in Mrican Village, Ponorogo Regency. This program was implemented by the Mathematics Community Research (MCR) of Universitas Muhammadiyah Ponorogo (UMPO) under the 2024 Student Organization Capacity Strengthening Program (PPK Ormawa). With a participatory approach, students act as facilitators in digitizing waste bank management, which was previously done manually and inefficiently. The Zerowastemate application enables transparent and efficient waste management by digitally recording waste type, weight, and value. It promotes community participation in cleanliness and waste reduction, while increasing household income through waste savings. This program demonstrates how digital technology enhances both environmental and economic aspects in villages, highlighting the vital role of collaboration between students, technology, and communities in achieving sustainable development. The research method involved selecting participants, collecting data through interviews, observations, and documentation, and then analyzing the data thematically. Triangulation ensured validity, while a descriptive narrative captured the impact. The program shows how student-led digital innovation drives sustainable, community-based environmental and economic change.